2001
DOI: 10.1242/jcs.114.20.3695
|View full text |Cite
|
Sign up to set email alerts
|

Synapsin I is expressed in epithelial cells: localization to a unique trans-Golgi compartment

Abstract: Synapsin I is abundant in neural tissues. Its phosphorylation is thought to regulate synaptic vesicle exocytosis in the pre-synaptic terminal by mediating vesicle tethering to the cytoskeleton. Using anti-synapsin antibodies, we detected an 85 kDa protein in liver cells and identified it as synapsin I. Like brain synapsin I, non-neuronal synapsin I is phosphorylated in vitro by protein kinase A and yields identical 32P-peptide maps after limited proteolysis. We also detected synapsin I mRNA in liver by norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…We found that all promoters initiate transgene expression in cultured HEK293T cells, including weak expression by SYN. There are a few possible explanations why this neuronal-specific promoter still initiated weak expression in these cells derived from humanembryonic kidney: (1) the high copy-number of the transgene due to the plasmid DNA transfection may be responsible for leaky expression; (2) ITR sequences in the plasmid DNA have weak promoter activity themselves [65,66] and may cause expression in these non-neuronal cells; (3) there are reports that the SYN promoter can initiate expression in non-neuronal cells such as hepatocytes after high-dose and systemic administration [67][68][69]. In contrast to observations in HEK293T cells, we've previously demonstrated that the SYN promoter does initiate strong transgene expression in cultured CNS neurons [45].…”
Section: Discussionmentioning
confidence: 99%
“…We found that all promoters initiate transgene expression in cultured HEK293T cells, including weak expression by SYN. There are a few possible explanations why this neuronal-specific promoter still initiated weak expression in these cells derived from humanembryonic kidney: (1) the high copy-number of the transgene due to the plasmid DNA transfection may be responsible for leaky expression; (2) ITR sequences in the plasmid DNA have weak promoter activity themselves [65,66] and may cause expression in these non-neuronal cells; (3) there are reports that the SYN promoter can initiate expression in non-neuronal cells such as hepatocytes after high-dose and systemic administration [67][68][69]. In contrast to observations in HEK293T cells, we've previously demonstrated that the SYN promoter does initiate strong transgene expression in cultured CNS neurons [45].…”
Section: Discussionmentioning
confidence: 99%
“…Syn I has been also found in osteoblasts, which are able to trigger glutamate release via molecular mechanisms strikingly similar to those of synaptic neurotransmission (Bhangu et al, 2001), and synapsin-like proteins have been identified on rat liver endosomes (Matovcik et al, 1994). In epithelial cells, syn I localises on a trans-Golgi network (TGN)-associated compartment, where it might mediate post-TGN trafficking routes (Bustos et al, 2001). Finally, syn I is also present in non-neuronal cell lines such as HeLa or NIH/3T3, where it is associated with cytoskeletal components, in particular to the actin cytoskeleton (Hurley et al, 2004).…”
Section: Expression and Regulationmentioning
confidence: 99%
“…A second possibility is that the AAV-BDNF spreads through the blood system. The expression of BDNF in the blood vessels was proposed by Cefis et al [ 76 ], and should be taken into consideration in our experimental model, as we used the synapsin promoter to express BDNF, and synapsin-1 has also been reported to be expressed in the epithelial cells of blood vessels [ 80 ].…”
Section: Discussionmentioning
confidence: 99%